2020
DOI: 10.1080/03007995.2020.1771293
|View full text |Cite
|
Sign up to set email alerts
|

Long-term direct and indirect costs of ulcerative colitis in a privately-insured United States population

Abstract: Objective: Prior evaluations of ulcerative colitis (UC)-related costs are dated or encompassed limited follow-up. This study assessed the incremental direct and indirect work loss-related costs of privatelyinsured patients with UC in the United States, overall and in specific subgroups. Methods: In this retrospective matched cohort study, the OptumHealth Care Solutions, Inc (formerly Optum Health Reporting and Insights employer) database (01 January 1999-31 March 2017) was used to identify adult patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
(54 reference statements)
0
16
0
Order By: Relevance
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 4837 studies were screened on title and abstract and 4730 excluded. After full‐text screening, 64 of the remaining 107 studies were included in the systematic review 32‐95 . No missed studies were found in the reference lists of the other systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Longitudinal data to assess changes in total and component costs for incident cases were not available for different time periods. Most studies reported annual healthcare costs for incident cases in the time period 2008-2012, 42,47,70,71,73,76,92,93,95 and other incidencebased studies reported healthcare costs in the first ten years after diagnosis. 67,77 Mean annual IBD-attributable costs of incident CD and UC cases in the first year after diagnosis were assessed in seven studies (Table 3).…”
Section: Healthcare Costsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with inflammatory bowel disease (IBD) experience lower HRQoL; higher absenteeism, presenteeism, and work and activity impairment; higher HRU; and higher direct and indirect costs compared with the general population [17,[44][45][46][47]. However, comparing IBD with other diseases may reveal the true burden of IBD on society.…”
Section: Plos Onementioning
confidence: 99%